2011
DOI: 10.1007/s12439-011-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Een handreiking voor familieleden over palliatieve zorg bij dementie: evaluatie door zorgverleners en familieleden

Abstract: Families of nursing home residents with dementia are usually involved in care and treatment decisions. To this end, family needs to be informed on the course of the dementia and possible palliative care. Based on a Canadian booklet, we developed an adapted version for use in the Netherlands. Elderly care physicians (n = 30), nurses (n = 38), and bereaved families (n = 59) evaluated the booklet and possible implementation strategies. All respondents confirmed that in general, there is a need of an information b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 27 publications
0
22
0
5
Order By: Relevance
“… Van der Steen et al (2012) [ 57 ] Canada Netherlands Italy Family booklet on comfort care in dementia The booklet was found highly acceptable and useful by Canadian and Dutch families, but less so by Italian families. Van der Steen et al (2011) [ 58 ] Netherlands Family booklet on comfort care in dementia There was a great need for written explanation about palliative care in dementia. The booklet is seen as suitable and useful.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Van der Steen et al (2012) [ 57 ] Canada Netherlands Italy Family booklet on comfort care in dementia The booklet was found highly acceptable and useful by Canadian and Dutch families, but less so by Italian families. Van der Steen et al (2011) [ 58 ] Netherlands Family booklet on comfort care in dementia There was a great need for written explanation about palliative care in dementia. The booklet is seen as suitable and useful.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 24 different interventions were tested in the included studies. In two studies [ 57 , 58 ], the same data set and findings were presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3), 38,47,51 telephone questionnaires (n = 1), 45 and online surveys (n = 1). 43 Sample sizes ranged from one 46 to 188 50 , with the qualitative studies having smaller samples.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In all, seven unique interventions across 11 studies were identified. A booklet about comfort care in advanced dementia [49][50][51][52] and a psychoeducational programme 38,47 were evaluated in multiple studies.…”
Section: Interventions To Support Family Caregivers In Included Studiesmentioning
confidence: 99%